PELATIHAN KESIAPSIAGAAN BENCANA BAGI MASYARAKAT PESISIR PANTAI DI KELURAHAN OESAPA - Rima Nindia Selan (Jurnal Pengabdian Vokasi, 2021)
Oesapa Beach is a tourist destination beach located in Kelapa Lima District, Kupang City. The location of Oesapa Beach is on the coast of the Kupang bay which is quite close to the South Beach (Indian Ocean). Therefore, Oesapa Beach is also very vulnerable to coastal disasters, so there is a need for early coastal disaster counseling efforts for the coastal communities of Oesapa Beach, so that the community has a spirit of being ready and responding to emergencies in the event of a disaster. Many of them live and open businesses on the coast and based on the results of interviews with the community, they still do not know about disaster emergency preparedness and response. Reflecting on the disaster that occurred last April, the community service activity (PKM) this time is very important because it has the main goal of providing counseling about important things that need to be known by the community around the coast about coastal disaster management, both before the disaster, during a disaster or after a disaster. It also aims to build a spirit of readiness and readiness to survive by the appeal from the government. The main activities are counseling about disasters and disaster preparedness actions from experts who have experience and explanations through simulation videos about what things must be done when a disaster occurs so that people understand and are better prepared to deal with disasters. The target to be achieved as the output of this training program is to increase partners' knowledge of disaster emergency preparedness and response, as well as produce modules that can be used as information media on disaster preparedness. With this PKM activity, it is hoped that it will increase the knowledge of the coastal community of Oesapa about disasters and prepare themselves, families, communities in dealing with disasters.